Islamic Educational Administration and Management Program, Prince of Songkla University (PSU): Contributions and Challenges for Malay Muslim Community in Thailand - Niloh Wae-u-seng; Abdulhakam Henpiya; Samsoo Sa-U (Jurnal Pendidikan Islam, 2019)
In Thailand context, Faculty of Islamic Sciences (FIS), Prince of Songkla University, Pattani Campus, is one of the higher educational institutions which plays a vital role not only in disseminating knowledge related to Islamic studies disciplines but also serving as an impetus to the development of Muslim community in southern part of Thailand in particular. This study aims at examining the ongoing development of one of the programs offered by FIS i.e., Islamic Educational Administration and Management Program. The focus will be given to its contribution and proposal for the development that would result in strengthening the program to achieve the desired goal. Documentary analysis is used for the study. Moreover, presentation of the result will be narratively described. It is hoped that the study would give some guidelines for policy implication.